Do Investors Herd: Evidence from an Emerging Market - Safi Ullah Khan; Muhammad Faisal Rizwan (The Lahore Journal of Business)
Employing stock price data from a developing market, we examine whether investors’ trading patterns are characterized as herd behavior at the market and industry levels. Unlike results for some developing markets, linear models of herd behavior find no evidence of herd formation, in any of the sectors, during periods of large market movements. However, non-linear models find significant nonlinear herding behavior only for two sectors of the whole sample, and when we group the sub-samples based on up and down market movements. Overall, empirical results tend to support the notion of no herd formation in Pakistan’s market. Two main explanations may be offered for the results: first, a developing market, characterized by thin trading and low turnover, with few of the stocks from various sectors actively traded in the market. Second, individual investors that dominate Pakistan’s equity market and low levels of institutional investor’s presence preclude herd formations.